karkis21
karkis21
19-06-2020
SAT
contestada
f(x) = (x + 1)(2x + 6)(x - 1)(x – 4)2
Respuesta :
alisashatravka
alisashatravka
19-06-2020
0=(x+1)(2x+6)(x-1)(x-4)*2
X1=-3
X2= -1
X3=1
X4=4
Answer Link
lindagottlieb16
lindagottlieb16
19-06-2020
Answer:
Explanation: I include all my steps in the picture I attached
Answer Link
VER TODAS LAS RESPUESTAS ( 79+ )
ACCESS MORE
Otras preguntas
How does graphing linear inequalities differ from graphing linear equations?
Is 2,5,11 linear or nonlinear
Convergent plate movement can create all of the following EXCEPT A) ridges B) valleys C) mountains D) volcanoes.
Which of the lines below is a line of symmetry? A. Red B. Yellow C. Neither D. Both
evaluate the given expression if x=25, y=10, w=45, and z=10 (x-y)^2+10wz
Here is a list of numbers. 32 29 20 30 37 34 33 31 Tanya thinks that to work out the median, she simply needs to find the middle number. So she says that "37" i
In the policymaking process, the stage in which a bureaucratic agency translates law action through the adoption of administrative regulations and the regulatio
When push-starting your car, what is the 3rd Law partner to the friction force you exert on the ground? A) The horizontal force you exert on the car. B) The no
what is a reason landowners would rather have slaves than indentured servants
On an acceleration-time graph, what are the units for acceleration